Clinical Overview of GIST and Its Latest Management by Endoscopic Resection in Upper GI: A Literature Review - Cicilia Marcella; Rui Hua Shi; Shakeel Sarwar (Gastroenterology Research and Practice)
Aims. To review the clinical presentation, diagnosis, assessment of risk of malignancy, and recent advances in management (mainly focusing on the role of endoscopic resection) of gastrointestinal stromal tumors (GISTs) in upper GI. Method. We searched Embase, Web of science, and PubMed databases from 1993 to 2018 by using the following keywords: “gastrointestinal stromal tumors,” “GIST,” “treatment,” and “diagnosis.” Additional papers were searched manually from references of the related articles. Findings. The improvement of endoscopic techniques in treating upper gastrointestinal subepithelial tumors especially gastrointestinal tumors has reduced the need for invasive surgery in patients unfit for surgery. Many studies have concluded that modified endoscopic treatments are effective and safe. These treatments permit minimal tissue resection, better dissection control, and high rates of en bloc resection with an acceptable rate of complications.